Findings of the Association for Computational Linguistics: EMNLP 2021 2021
DOI: 10.18653/v1/2021.findings-emnlp.313
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Pretrained Models for Automatic Summarization of Doctor-Patient Conversations

Abstract: Fine-tuning pretrained models for automatically summarizing doctor-patient conversation transcripts presents many challenges: limited training data, significant domain shift, long and noisy transcripts, and high target summary variability. In this paper, we explore the feasibility of using pretrained transformer models for automatically summarizing doctorpatient conversations directly from transcripts. We show that fluent and adequate summaries can be generated with limited training data by fine-tuning BART on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…For example, only 3 papers explicitly mention the need for human oversight in system deployment, and only 2 of these describe the stakeholders who would be responsible for supervision with one paper noting that "[t]he most natural application of this technology is not as a replacement for a human scribe, but as an assistant to one. By providing tools that aid a human scribe one can mitigate much of the risk of system failures, such as hallucination" (Zhang et al, 2021a). Ethical considerations not grounded in use contexts may not be able to realistically anticipate adverse impacts.…”
Section: Limitations and Ethical Considerationsmentioning
confidence: 99%
“…For example, only 3 papers explicitly mention the need for human oversight in system deployment, and only 2 of these describe the stakeholders who would be responsible for supervision with one paper noting that "[t]he most natural application of this technology is not as a replacement for a human scribe, but as an assistant to one. By providing tools that aid a human scribe one can mitigate much of the risk of system failures, such as hallucination" (Zhang et al, 2021a). Ethical considerations not grounded in use contexts may not be able to realistically anticipate adverse impacts.…”
Section: Limitations and Ethical Considerationsmentioning
confidence: 99%
“…(Joshi et al, 2020a) showed that the quality of generated summaries can be improved by encouraging copying in the pointer-generator network. Lastly, (Zhang et al, 2021) describe an abstractive approach based on BART, in which a two-stage summary model is created. The resulting models greatly surpass the performance of an average human annotator and the quality of previously published work for the task.…”
Section: Related Workmentioning
confidence: 99%
“…The method used in document summarization can be directly transferred into dialogue summarization. Zhang et al [216] first truncate the dialog into several chunks and summarize each chuck into partial summaries. Then they rewrite these partial summaries into a complete summary.…”
Section: Text Summarizationmentioning
confidence: 99%